Securitização do crédito como tecnologia para o desenvolvimento do agronegócio: proteção jurídica do investimento privado - Buranello, Renato Macedo (2015)
The purpose of this dissertation is to describe the operating development and to identify institutional shortfalls in Brazil’s rural credit market. According to this study, the establishment of the National Rural Credit System (SNCR) has brought forth advances and the enactment of Law 11,076, of December 31, 2004, has provided for a new relationship with the financial and capital market, from the perspective of the necessary break with the former system. Research conducted for this dissertation differs from the traditional legal approach, which singles out the assessment of financial transactions. Credit is assessed herein as an instrument of public policy, in planning the activity to develop agribusiness. This study also intended to innovate by including a broad discussion on the economic foundations and legal technology in the organization of the Private System for the Financing of Agribusiness and the securitization of receivables to mobilize crops and risk mitigation mechanisms. This dissertation includes the assessment of the rural credit bonds that are part of such system, which provide for the diversified distribution of both physical and financial resources among producers, private enterprises and financial agents alike. Additionally, this study highlights that the instruments currently available to mobilize credit and diversify risks have guaranteed the supply of a substantial portion of the funds, including in markets with diversified risks and greater complexity, as is the case of the markets of the Agroindustry Systems. Having focused on the development of the private credit market within the scope of the capital market as the main purpose of this dissertation, it has been possible to conclude that there is a break in the funding methods available in the Brazilian rural industry, especially in relation to the inputs of public policies and corporate strategies: i) gradual and proportional withdrawal of government-controlled funds; ii) entry of private companies in the industry, via trade credit; iii) increasingly direct relations between credit and the development of the rural debt capital market; and iv) use of mechanisms to reduce uncertainty, and credit safety